A Comparative Evaluation of Direct Pressure and Electrocautery Techniques for Hemorrhage Management in the Liver Bed during Laparoscopic Cholecystectomy - Hamidah Uref Rahila; Imam Bakhsh; Muhammad Bilal; Bushra Tasneem; Urooj Niazi; Raja Muhammad Adeel Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Gallstone disease is highly prevalent, with laparoscopic cholecystectomy (LC) being the standard treatment. Bleeding from the liver bed is a common intraoperative challenge, typically managed by direct pressure or electrocauterization. Objective To compare direct pressure and electrocauterization for liver bed hemostasis during LC, assessing intraoperative bleeding, postoperative bleeding, and pain. Study Design: randomized controlled trial Duration and place of study: This study was conducted in Peoples University of Medical and Health Sciences Nawabshah from July 2023 to July 2024 Methodology This randomized controlled trial conducted at our hospital. A total of 100 patients included in the study were divided into two groups: Group A (n=50) received gauze pressure, and Group B (n=50) received electrocauterization. Bleeding control and pain scores at 12 and 24 hours postoperatively were recorded. Results Mean ages were 40.5 ± 12.4 years (Group A) and 42.3 ± 10.5 years (Group B). Bleeding control was successful in 86% of Group A and 95% of Group B (p = 0.008). Group A had lower pain scores at both 12 and 24 hours (p = 0.0001). Conclusion Electrocauterization offers superior bleeding control, while direct pressure is associated with reduced postoperative pain.